Evidence for a Positive Relationship between Working-Memory Capacity and Detection of Low-Prevalence Targets in Visual Search. (January 2013) - Schwark, Jeremy; Sandry, Joshua; Dolgov, Igor
Our ability to detect a target in visual search relates to the prevalence of the target, whereby rare targets are missed more than common targets. The current study sought to identify operator characteristics that could account for the higher miss rates associated with rare targets. The results found that working-memory capacity, which is strongly related to attentional control and inhibition of irrelevant information, was significantly correlated with the ability to detect low-prevalence targets. High-capacity observers also exhibited lengthened target-absent responses with rare targets, suggesting that the high-capacity observers were more persistent in their searches than others.